Let students pay for their higher education: Debate concerning free and subsidized education based on sunk cost theory. Issue 4 (22nd October 2020) - Bhayani, Ali
Abstract : Governments across the world are grappling with the question about the funding of subsidized higher education (HE). Critics of free or subsidized HE have argued that higher rate of return of graduates serves as enough extrinsic motivation, adding, to the argument that the free or subsidized HE results in lack of intrinsic motivation. Further, critics support their assertion by citing lagging academic performance in countries where HE is free or heavily subsidized. Proponents of the state funding have cited the role of externalities and equal opportunities as the reason for subsidized HE. This study has used sunk cost theory to understand whether making students pay for their own education would impact on their performance and retention by enhancing intrinsic motivation in addition to analyzing the role of parents and the culture. Results indicate that students are impacted by sunk cost fallacy, as opposed to the earlier findings by Ketel et al. (2016), and that making them shoulder part of the tuition fees in form of contribution or student loans would result in "selection effects" where some sort of positive fee (after scholarships and grants) is paid by the students.